2018
DOI: 10.1186/s42492-018-0005-2
|View full text |Cite
|
Sign up to set email alerts
|

A non-uniform allowance allocation method based on interim state stiffness of machining features for NC programming of structural parts

Abstract: For thin-walled parts, uniform allowance to each machining surface is allocated by the traditional machining method. Considering the sequence of the adjacent machining features, it may cause poor stiffness for some side walls due to a minor wall thickness, which may cause the deformation of the final formed parts to be large, or deduce machining efficiency for some machining features due to too thick remains. In order to address this issue, a non-uniform allowance allocation method based on interim state stiff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…The priorities of each phase can all be met by doing so. (2) This research further enhances the recommendation of relative larger setting of machining allowance of rough machining, and small setting of finishing machining, like [4,26]. (3) It is revealed that the high-speed cutting technique recommended by many previous studies, like [13,30], are not always suitable for application.…”
Section: Discussionmentioning
confidence: 76%
See 2 more Smart Citations
“…The priorities of each phase can all be met by doing so. (2) This research further enhances the recommendation of relative larger setting of machining allowance of rough machining, and small setting of finishing machining, like [4,26]. (3) It is revealed that the high-speed cutting technique recommended by many previous studies, like [13,30], are not always suitable for application.…”
Section: Discussionmentioning
confidence: 76%
“…The value ranges of each sub-objective functions are listed in Table 15, and those can be used to calculate the normalized values by using Equation (26), and backwards as equal. Like the cylindrical turning, the number of the operation repeating time was set to be 100, namely n I = 100.…”
Section: Modeling Results Of Energy Consumption Of the Step Millingmentioning
confidence: 99%
See 1 more Smart Citation
“…This contributes to maintaining high stability, high rigidity, and long lifespan in its operational environment. To achieve these objectives, Jiang et al [1] proposed a method for non-uniform allocation of finishing allowances in thin-walled structural component precision machining based on the transitional state stiffness of machining features. This method effectively enhances the component's stiffness and reduces deformation.…”
Section: Introductionmentioning
confidence: 99%
“…They developed a linear-programming optimization model to optimize the overall machining deformation. Jiang et al [ 15 ] proposed a nonuniform allowance allocation method based on the interim state stiffness of machining features. Their proposed method can effectively improve the stiffness of a part and hence, reduce its deformation.…”
Section: Introductionmentioning
confidence: 99%